The Strategy of the God of Peace in Overcoming the Practice of Siri Marriage: A Study of Alue Kambuk Village, Suka Makmue, Nagan Raya - Nanda, Fitria; Djawas, Mursyid (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The phenomenon of nikah siri (unregistered marriage) remains a persistent social and legal issue in Aceh, particularly in Gampong Alue Kambuk, where many community members believe that a marriage is valid under Islamic law without official registration at the Office of Religious Affairs (KUA). This perception leads to legal uncertainty and weakens the protection of women’s and children’s rights. Such conditions reflect a gap between religious norms, customary practices, and state law, highlighting the strategic role of Tuha Peut as a customary institution in mediating and educating the community through religious and social approaches rooted in local wisdom.This study employed a qualitative method with an empirical-sociological approach, using primary data collected through in-depth interviews with the Geuchik (village head), Tuha Peut members, Tgk. Meunasah (village cleric), officials from the Suka Makmue Office of Religious Affairs, and local religious leaders. Secondary data were obtained from legal literature, books, and relevant academic journals. Data were gathered through interviews, participatory observation, and documentation, and analyzed using thematic analysis to identify the roles and strategies of Tuha Peut.The results indicate that Tuha Peut applies two types of strategies in addressing nikah siri: planned strategies and emergent strategies. Planned strategies are implemented through legal counseling, marriage registration campaigns, and religious guidance during village deliberations, while emergent strategies develop spontaneously through social communication, informal advice, and religious–customary mentorship. The main obstacles include low legal awareness, economic limitations, and strong traditional influences that prioritize religious legitimacy over state law. The study concludes that Tuha Peut plays a strategic mediating role that bridges religious, customary, and state legal systems, functioning as both an educational and preventive institution in enhancing community legal awareness